Pendeteksian Suap di Lembaga Sektor Publik Indonesia: Peran Audit Investigasi dan Big Data - Briyan Efflin Syahputra; Anggit Esti Irawati (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2025)
Bribery continues to be a persistent issue in the Indonesian administration. Thus, research to determine the best techniques for bribery detection is still desperately needed. The purpose of this study was to examine how big data and investigative audits affect bribery detection, and the effect of big data on investigative audits. This study used a quantitative approach. A questionnaire was utilized as the data gathering tool in the survey method. The questionnaire was filled up by 199 auditors of BPK and BPKP RI. Assisted by the SmartPLS application, structural equation modelling (SEM) was the statistical test employed in this study. The results of this study indicate that both investigative audits and big data have been shown to have a positive effect on bribery detection. Furthermore, big data has also been shown to have a positive effect on investigative audits.